FENOMENA POLISEMIK BAHASA ARAB DALAM AL-QURAN - Hamdani, Wagino Hamid (Universitas Pendidikan Indonesia, 2012)
Abstrak Fenomena Polisemik Bahasa Arab dalam al-Quran. Artikel ini mengkaji fenomena polisemik bahasa Arab dalam al-Quran. Cakupan kajiannya meliputi 10 bentuk polisemik yang berwazan: fa’iil, fi’aal, fa’aan/fu’laan, fu’l, fa’alah, fu’uul tafa’la/tafa’al, tafa’aluu, af’al dan fa’al. Dari hasil analisis diperoleh variasi makna morfologis bagi setiap bentuk polisemik, yaitu: (1) bentuk fa’iil mengandung 5 makna morfologis; (2) bentuk fi’aal mengandung 4 makna morfologis; (3) bentuk fa’laan, fu’laan dan fi’laan mengandung 4 makna morfologis; bentuk fu’l mengandung 4 makna morfologis; (5) bentuk fa’alah mengandung 5 makna morfologis; (6) benuk fu’uul mengandung 4 makna morfologis; (7) bentuk tafa’al 5 makna morfologis; (8) bentuk tafa’aluu mengandung 8 makna morfologis; (9) bentuk af’al mengandung 10 makna morfologis; dan bentuk fa’al mengandung 5 makna morfologis. Makna morfologis setiap bentuk kata dapat teridentifikasi melalui distribusi morfologis, sarana sintaktis, dan mkna leksilak.Kata kunci: Fenomena polisemik, makna morfologis Abstract Phenomenon of Arabic Language Polysemy in the Quran. This paper that examined the phenomenon of Arabic polysemy in the Koran. Coverage of the study inclused 10 forms of polysemy: faiil, fiaal, falaan/fulaan/ fi’laan, fu’l, fa’alah, fu’uul tafa’la/tafa’al, tafa’aluu, afal and fa’al. Obtained from the results of the analysis are morphological variations in meaning for every from of polysemy, namely: (1) the faiil from contains 5 morphological meanings, (2) the fiaal form contains 4 morphological meanings, (3) forms offalaan, fulaan and filaan contains 4 morphological meaning,; (4) the form of fu’l contains 4 morphological meanings, (5) the form of fa’alah contains 5 morphological meanings, (6) the form fu’uul contains 4 morphological meanings, (7) the form of tafaal contains 5 morphological meanings, (8) the form of tafaaluu contains 8 morphological meanings; (9) the form of afal contains 10 forms morphological meanings, and the form of fa’al contains 5 morphological meanings. Morphological meanings of each form of words can be identified through the morphological distribution, syntatic means, and lexical meaning.Keywords: polisemik phenomenon, meaning of morphologically